Local anesthesia associated with cutaneous biopsy in veterinary medicine: a narrative review (Research, Society and Development, 2022)
Skin biopsies, especially by punch, are widely used as a diagnostic tool in veterinary dermatology. It can be performed in patients under general anesthesia combined or not with local anesthesia, and in some cases, with local anesthesia alone. Lidocaine is the most widely used local anesthetic due to its rapid onset of action, easy to access and relatively inexpensive cost. Infiltrative anesthesia is often used in dermatological procedures, but regional anesthesia and topical anesthesia may also be recommended in some cases. Adverse effects vary from uncommon to rare and include local reactions such as local nerve lesions and hypersensitivity or contact dermatitis, and systemic reactions namely anaphylaxis, cardiotoxicity, and central nervous system depression. When administered at the appropriate dose for the referred species, with standardized technique and anatomical knowledge, adverse reactions are extremely rare. Local anesthetics are of fundamental importance for veterinary dermatology, especially in skin biopsy of dogs and cats. The aim of this narrative review, is to explore the structure and mechanism of action of the main drugs used, local anesthesia techniques, as well as possible side effects associated with the use of these drugs in dermatological surgeries, with focus on skin biopsies.